1995
DOI: 10.1111/j.1365-263x.1995.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and prolonged breast‐feeding in 18‐month‐old Swedish children

Abstract: Summary. Three thousand children aged 18 months were screened for dental caries and ongoing breast‐feeding at 46 child welfare centres in different parts of Sweden. Of these, 200 children were selected for a more comprehensive examination, involving investigation of dietary, toothbrushing and sucking habits, use of fluoride, and determination of salivary levels of mutans streptococci and lactobacilli. The children were divided into four groups: group 1: children with caries not being breast‐fed; group 2: chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
3
19
0
4
Order By: Relevance
“…These studies involving children have shown that ECC is associated with increases in the proportions of acidogenic bacteria and high acidogenic potential, in agreement with the ecological plaque hypothesis of caries [Marsh, 2006]. Considering that the presence of S. mutans in biofilms in ECC is associated with a high level of sucrose exposure [Parisotto et al, 2010[Parisotto et al, , 2015, our data suggest that ECC children are subjected to additional dietary sugar challenges than only lactose from milk [Hallonsten et al, 1995]. However, ECC and caries-free children did not differ regarding resting biofilm pH.…”
Section: Discussionsupporting
confidence: 73%
“…These studies involving children have shown that ECC is associated with increases in the proportions of acidogenic bacteria and high acidogenic potential, in agreement with the ecological plaque hypothesis of caries [Marsh, 2006]. Considering that the presence of S. mutans in biofilms in ECC is associated with a high level of sucrose exposure [Parisotto et al, 2010[Parisotto et al, , 2015, our data suggest that ECC children are subjected to additional dietary sugar challenges than only lactose from milk [Hallonsten et al, 1995]. However, ECC and caries-free children did not differ regarding resting biofilm pH.…”
Section: Discussionsupporting
confidence: 73%
“…0.001) and a significantly higher incisors, similar to classic 'nursing bottle caries' in bottlefed infants [Gardener et al, 1977;Kotlow, 1977;Brams and Maloney, 1983]. Some investigators have observed an increased risk and severity of caries associated with prolonged breast-feeding and night breast-feeding [Matee et al, 1994;Hallonsten et al, 1995;Weerheijm et al, 1998;Dini et al, 2000;Sayegh et al, 2004]. A systematic review of controlled human studies comparing different modes of infant feeding, however, found a poor quality of published studies and no conclusive evidence of beneficial or harmful effects of breast-feeding [Valaitis et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The length of breast and bottle feeding may play a role to caries development. Various studies have been demonstrated late weaning e.g., between 12 and 36 months was associated with caries (27).…”
Section: Etiologymentioning
confidence: 99%